Depresión y consumo de drogas legales en estudiantes del Colegio Manuel Cabrera Lozano de Loja - Peláez Salinas, Yadira Paola (2014)
The present investigation called DEPRESSION AND LEGAL DRUG CONSUMPTION IN HIGH SCHOOL STUDENTS MANUEL CABRERA LOZANO DE LOJA, main objective was to establish the relationship between depression and drug use. The investigation was quantitative descriptive and cross sectional was conducted at the College, in the period from February to August 2013, where 267 students were surveyed them that met all inclusion criteria. The result being that most cases mild, moderate and severe depression, are related to adolescents who use alcohol and snuff simultaneously, the majority of students having moderate depression are male, the majority of students with mild and severe depression are female. Men and women with moderate depression, men with mild depression and women with severe depression, higher percentage affects students aged 15-17. Men with severe depression and women with mild depression higher percentage affect students between 12-14 and 15-17 years. Alcohol consumption is higher in women and consumption of snuff and both substances is higher in men, the age group most vulnerable to this consumption in both genders is between 15-17 years. Of the total population 22.8 % have depressive problems. KEYWORDS • Depression • Legal Drug • Students